PRODUKTIVITAS DAN KONTRIBUSI PENGOLAHAN ANYAMAN PURUN (Lepironia articulatta Domin) TERHADAP PENDAPATAN MASYARAKAT DI DESA SUNGAI RUTAS KABUPATEN TAPIN - Ahmadi Ahmadi; Adi Rahmadi; Fatriani Fatriani (Universitas Lambung Mangkurat, 2019)
ABSTRACT. This study aims to determine the productivity and contribution of woven purun (Lepironia articulatta Domin) to the income of the community. The method used by observation in central woven craft purun and interview method based on questionnaires on the respondents woven craftsmen purun respondents taken 100% of the number of craftsmen made crafts there are two that is woven mat mats and respondents craftsman mat woven there are 8 people and craftsman woven hat 14 person. Productivity of mats ranges from 0.085 pieces / hour, to 0.101 pieces per hour. The highest productivity of the respondents was 0.101 fruit/hour, the lowest was 0.085 fruit/hour. The productivity of hat making ranges from 1,035 pieces / hour, to 1,364 pieces/hour. The highest productivity of Fajarianti 1,364 respondents/hour, the lowest of Asniah 1,035 respondents per hour. Net income making mats ranging from IDR 2,300,000.00 to IDR 2,863,500.00. The highest income of respondents Marsiah IDR 2.863.500,00 per year lowest respondents Dariah IDR 2.300.000,00 per year. Net income of hat making ranges from IDR2.180.854,00 to IDR 3,512,760.00. The highest income respondents Fajarianti IDR 3.512.760,00 per year, the lowest income respondents Salamiah IDR 2,180,354.00 per year. The contribution of woven mats decreased an average of 30.30%. The highest respondent Laila Hastuti is 36.28%, the lowest respondent is Arniah 26.44%, the average contribution of the hat is 30.01%. Highest respondent Aisyah is 45.37%, the lowest responder Salamiah is 18.51% Keywords: purun; productivity; income ABSTRAK. Penelitian ini bertujuan untuk mengetahui produktivitas dan kontribusi pengolahan anyaman purun (Lepironia articulatta Domin) terhadap pendapatan masyarakat. Metode yang digunakan observasi di sentral kerajinan anyaman purun dan metode wawancara berdasar kuesioner pada responden pengrajin anyaman purun responden diambil 100% dari jumlah pengrajin jenis kerajinan yang dibuat ada dua yaitu kerajinan anyaman tikar dan topi responden pengrajin anyaman tikar ada 8 orang dan pengrajin anyaman topi 14 orang. Produktivitas pembuatan tikar berkisar antara 0,085 buah/jam, sampai 0,101 buah/jam. Produktivitas tertinggi responden Arniah 0,101 buah/jam, terendah Dariah 0,085 buah/jam. Produktivitas pembuatan topi berkisar 1,035 buah/jam, sampai 1,364 buah/jam. Produktivitas tertinggi responden Fajarianti 1,364 buah/jam, terendah Responden Asniah 1,035 buah/jam. Pendapatan bersih pembuatan tikar berkisar antara Rp.2.300.000,00 sampai Rp.2.863.500,00. Pendapatan tertinggi responden Marsiah Rp.2.863.500,00 pertahun terendah responden Dariah Rp.2.300.000,00 pertahun. Pendapatan bersih pembuatan topi berkisar antara Rp 2.180.854,00 sampai Rp. 3.512.760,00. Pendapatan tertinggi responden Fajarianti Rp. 3.512.760,00 pertahun, pendapatan terendah responden Salamiah Rp. 2.180.354,00 pertahun. Kontribusi anyaman tikar purun rata-rata 30,30%. Tertinggi responden Laila Hastuti sebesar 36,28%, terendah responden Arniah 26,44%, kontribusi topi purun rata-rata 30,01%.Tertinggi responden Aisyah sebesar 45,37% , terendah responden Salamiah sebesar 18,51%. Kata kunci : purun; produktivitas; pendapatan